Komunikasi Efektif dalam Meningkatkan Literasi Kesehatan Mental - Sarah Bryna Grace; Ade Gandha Kurnia Tandra; Mary Mary (Jurnal Komunikasi, 2020)
This article is the result of a communication study research on effective communication conducted by the Into The Light Indonesia community on improving the mental health literacy of young people in Jabodetabek. Mental health in Indonesia has not received enough attention, unlike physical health, so it is necessary to increase understanding of mental health. Since 2013, the Into The Light Indonesia community has been present as a community of young people working as a center for advocacy, study and education on suicide prevention and working on mental health issues in Indonesia. This study aims to reveal differences in mental health literacy levels between young people in Jabodetabek who participate and those who do not participate in Into The Light Indonesia community’s activities, reveal the relationship of effective communication with the delivery of mental health literacy related materials, and to evaluate the communication strategy of Into The Light Indonesia community. For this reason, the research method used is a convergent parallel mixed method, in which a quantitative approach by taking two independent samples (???? = 120) to fill out a questionnaire to compare the level of mental health literacy and measure the effectiveness of communication carried out, as well as a qualitative approach through interviews to identify and evaluate the activities carried out by the Into The Light Indonesia community. The results of this study indicate that statistically, there is no significant difference between the mental health literacy levels of participants and non-participants in the Into The Light Indonesia community activities. However, the results of the study show that effective communication significantly increases the level of mental health literacy. Into The Light participants also showed awareness and interest in finding out more mental health related information. In this study it can also be found that a communication strategy approach is needed by adopting local ways to increase audience awareness and interest, as well as quantitative evaluation with clear measurements to measure the achievement of the communication strategy objectives. Artikel ini merupakan hasil penelitian studi komunikasi mengenai komunikasi efektif yang dilakukan oleh komunitas Into The Light Indonesia dalam meningkatkan literasi kesehatan mental anak muda di Jabodetabek. Kesehatan mental di Indonesia masih belum mendapat cukup perhatian layaknya kesehatan fisik, sehingga diperlukan peningkatan pemahaman mengenai kesehatan mental. Sejak tahun 2013, komunitas Into The Light Indonesia hadir sebagai sebuah komunitas orang muda yang bergerak sebagai pusat advokasi, kajian, dan edukasi pencegahan bunuh diri dan berkecimpung pada isu kesehatan mental di Indonesia. Penelitian ini bertujuan untuk mengungkap perbedaan tingkat literasi kesehatan mental antara orang muda di Jabodetabek yang berpartisipasi dengan yang tidak berpartisipasi dalam kegiatan komunitas Into The Light Indonesia, mengungkap hubungan komunikasi efektif dalam penyampaian materi terhadap literasi kesehatan mental, dan mengevaluasi strategi komunikasi komunitas Into The Light Indonesia. Untuk itu, metode penelitian yang digunakan adalah metode campuran paralel konvergen, dimana pendekatan kuantitatif dengan mengambil dua sampel independen (???? = 120) untuk mengisi kuesioner untuk membandingkan tingkat literasi kesehatan mental dan mengukur efektivitas komunikasi yang dilakukan, serta pendekatan kualitatif melalui wawancara untuk mengidentifikasi serta mengevaluasi kegiatan-kegiatan yang dilakukan komunitas Into The Light Indonesia. Hasil penelitian ini menunjukkan bahwa secara statistik, tidak ada perbedaan yang signifikan antara tingkat literasi kesehatan mental partisipan dan nonpartisipan kegiatan komunitas Into The Light Indonesia. Namun, hasil penelitian menunjukkan bahwa komunikasi efektif meningkatkan tingkat literasi kesehatan mental secara signifikan. Terlihat juga adanya awareness dan interest untuk mencari informasi lebih banyak mengenai kesehatan mental pada partisipan kegiatan Into The Light Indonesia. Dalam penelitian ini juga dapat ditemukan bahwa diperlukan pendekatan strategi komunikasi dengan mengadopsi cara-cara lokal untuk meningkatkan awareness dan minat audience, serta evaluasi kuantitatif dengan measurement yang jelas untuk mengukur ketercapaiannya tujuan strategi komunikasi.